Peran Kegiatan Komunitas Sraddha Sala Dalam Menjaga Kelestarian Sastra Jawa - Tri Wiyani; Yuhastina Yuhastina; Nurhadi Nurhadi (Mahesa Research Center, 2022)
The purpose of this study was to determine the role of Sraddha Sala Community activities in preserving Javanese literature in Surakarta City. The approach used is descriptive qualitative. The object of this research is the Sraddha Sala Community which is engaged in the preservation of Javanese literature. Sources of data in this study are people who are directly and indirectly involved in the activities of the Sraddha Sala Community. In collecting the data, the author uses several data collection techniques, namely documentation, observation, interviews. Analysis of the data in this study using analytical techniques from Milles and Huberman, by going through several paths, namely data condensation, data presentation, conclusion drawing/verification. In this study, the researchers focused on the activities carried out by the Sraddha Sala Community as an effort to preserve Javanese literature. In carrying out the activity, there are several factors that affect the running of the activity, namely: founder, network, cultural awareness. These factors greatly affect Sraddha's activities which include: Research, Classes, field studies, and Writing on social media. The activities of the Sraddha Sala Community as an effort to preserve Javanese literature are open to the general public.